Possible involvement of viral infection in the pathogenesis of myasthenia gravis - Maria Dolci; Lucia Signorini; Federica Perego; Sara Passerini; Chiara Giannasi; Francesca Camurri; Alessia Berni; Sara Messina; Valeria Pietropaolo; Alessandro Baj; Paola Cavalcante; Serena Delbue (Journal of NeuroVirology, 2026)
Myasthenia gravis (MG) is a chronic autoimmune disorder that involves the targeting of neuromuscular junctions and is primarily driven by autoantibodies against the acetylcholine receptor (AChR). While genetic susceptibility is a factor, environmental triggers, particularly viral infections, are being increasingly investigated as potential contributors to MG pathogenesis. This review examines the complex interplay between viral pathogens and MG, highlighting mechanisms such as molecular mimicry, bystander activation, and the aberrant stimulation of innate immune pathways via Toll-like receptors (TLRs). Key DNA viruses, including Epstein‒Barr virus (EBV) and parvovirus B19, have been detected within hyperplastic thymic tissues and thymomas, suggesting that they may sustain local autoreactive B-cell activation. Furthermore, recent clinical data emphasize the role of RNA viruses, most notably SARS-CoV-2, as significant triggers of new-onset MG and myasthenic crises. Despite substantial evidence linking viral infections to MG, further mechanistic research and large-scale observational studies are needed to definitively establish causality and refine therapeutic strategies targeting these virus-induced immune responses.

Susceptibility or resistance to Bartonella spp. infection in cats: Does the phenotype-B blood matter? - Eva Spada; Daniela Proverbio; Roberta Perego; Luciana Baggiani; Marta Meropiali; Paola Galluzzo; Rosalia D’Agostino; Carmela Sciacca; Valeria Blanda; Francesca Grippi (Comparative Immunology, Microbiology and Infectious Diseases, 2026)